Alelopatia de exsudatos de sementes de espécies usadas em restauração ecológica de áreas degradadas com sistema de semeadura por muvuca - Valmorbida, Raquel (2016)
Muvuca is a seed sowing technique of various tree species succession of distinct stages, together with species of green manure, in order to restore a degraded area. In this seeding technique, there can be biological interaction exudates, seeds and seedlings adjunct, different species of which may be mutually benefit or impaired, as germination and early development. An attempt was made in this study to investigate the allelopathic potential of exudates of Cajanus cajan seeds and Bauhinia forficata on bioindicator species (Solanum lycopersicum - tomato); and the allelopathic effect of these same exudates on forest species (Bauhinia forficata and Parapiptadenia rigida). The experiment was conducted in the laboratory, and the treatments were: control; exudates of Phase I and II of the soaking curve of C. cajan seeds and B. forficata, who underwent pH testing, electrical conductivity and phytochemical screening. The bioindicator species subjected to treatment was evaluated for germination, early growth, antioxidant enzyme activity and lipid peroxidation. Forest species subjected to the treatments were evaluated for germination and early development. According to the electrical conductivity, a greater release of exudates of precursor species in phase II of soaking. All exudates showed allelochemicals in its composition. As for the allelopathic potential, it is concluded that the exudates of C. cajan seeds and B. forficata not adversely affect germination, early growth and antioxidant enzyme activity of bioindicator, on the contrary, benefited performance these variables evaluated tomato. As for the allelopathic effect, the exudate of phase I of soaking C. cajan, and phases I and II of the seeds of B. forficata stimulated shoot length P. rigida. However, the exudate of the soaking stage II seeds of C. cajan, negatively affected the germination and initial development B. forficata. And still retarded germination of P. rigida.